Improving Students Speaking Skill Through Role-Play in Universitas Teknologi Mataram - Hijriati, Sartika (ANWARUL, 2022)
Speaking is one of tough skills that should be mastered by students in learning English. The aim of the research is to improve student’s speaking skill through role play technique. The subjects of this research were 24 students at the third semester of Secretary Department of Universitas Teknologi Mataram Academic Year 2019/2020. The result showed that there was a significant improvement of student’s speaking skill after using role play technique in teaching learning process. The students are able to speak in English fluently and confidently. The finding shows that role-play teaching technique is work well and can be applied to improve students speaking skill.